2015
DOI: 10.1080/10826076.2015.1028295
|View full text |Cite
|
Sign up to set email alerts
|

Separation, Identification, and Investigation of Antioxidant Ability of Plant Extract Components Using TLC, LC–MS, and TLC–DPPH

Abstract: Ten common phenolic compounds from five plant extracts i.e. Hypericum perforatum L., Matricaria recutita L., Achillea millefolium L., Thymus vulgaris L. and Salvia officinalis L. were separated using optimized TLC conditions and visualized using NP/PEG reagent.Antioxidant properties of components of the extracts were assessed using TLC-DPPH • directly on the TLC plate. Nine from ten analyzed polyphenols were proved to be radicalscavengers. The presence and identity of target substances in plant samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 32 publications
3
25
0
1
Order By: Relevance
“…However, there are some TLC studies which analysed the phenolic content of Hypericum species, including the study of Jesionek et al . and Males et al …”
Section: Thin‐layer Chromatographymentioning
confidence: 92%
See 1 more Smart Citation
“…However, there are some TLC studies which analysed the phenolic content of Hypericum species, including the study of Jesionek et al . and Males et al …”
Section: Thin‐layer Chromatographymentioning
confidence: 92%
“…The silica gel TLC plates were developed with seven different mobile phases and then derivatized with NP reagent and PEG reagent. The research team found that flavonoid aglycons like quercetin were better separated with the system toluene : diethyl ether : acetic acid (60 : 40 : 10 v/v/v), the flavonoid glycosides like rutin and hyperoside with the system ethyl acetate : acetic acid : formic acid : water (100 : 11 : 11 : 26 v/v/v/v) and the phenolic acids like chlorogenic acid with the system chloroform : ethyl acetate : acetone : formic acid (40 : 30 : 20 : 10 v/v/v/v) …”
Section: Thin‐layer Chromatographymentioning
confidence: 99%
“…Four other compounds (caffeic acid and apigenin in St. John wort and apigenin and apigenin 7-O-glucoside in sage) have been identified. Their presence was not revealed by TLC and it has been stated that their low level in the plant samples could be the reason [91]. …”
Section: Significant Analytical Applications To Plant and Plant Exmentioning
confidence: 99%
“…Traditional separation methods for polyphenols such as liquid-liquid extraction (Sun, Ferrão, & Spranger, 2003;Sun et al, 2006), thin-layer chromatography (Jesionek, Majer-Dziedzic, & Choma, 2015;Sun, Leandro, Ricardo-da-Silva, & Spranger, 1998), column chromatography (Lu & Foo, 1999;Sun, Belchior, Ricardo-da-Silva, & Spranger, 1999), semi-preparative and preparative HPLC (Makhotkina & Kilmartin, 2012;Sun, Belchior, et al, 1999) have disadvantages like timeconsuming, secondary-pollution, complex-process, low-yield and high-cost. High-speed counter-current chromatography (HSCCC), a supporting free liquid-liquid partition system where solutes are partitioned between two immiscible phases, offers various advantages such as high solute loading capability, high recovery, high repeatability and low solvent consumption (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%